Workshop Pelatihan Mikrokontroller Arduino dan ESP32 untuk Siswa SMP Islam Sawahan Turen - Azam Muzakhim Imammuddin; Septriandi Wirayoga; Moh. Abdullah Anshori; Isac Ilham Akbar Habibi; Guntur Yanuar Astono; Miftakhul Huda (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service initiative was carried out with the aim of introducing and training students of SMP Islam Sawahan Turen in programming and utilizing Arduino and ESP32 microcontrollers as a foundation for understanding modern technology. The workshop was specifically designed to provide students with knowledge of basic electronic concepts, sensors, and data communication, while also equipping them with practical skills to create simple microcontroller-based projects. During the sessions, participants received explanations about Arduino and ESP32, including how to connect sensors, process collected data, and transmit information to the Internet of Things (IoT) platform. In addition to the theoretical materials delivered, students were given opportunities to engage in direct practice under the guidance of experienced instructors, allowing them to gain a deeper comprehension of how the devices function. The combination of theory and practice helped students strengthen both their conceptual understanding and their technical abilities. Furthermore, the activity aimed to foster creativity and curiosity among participants in designing innovative projects that have real-life applications. This spirit of exploration is expected to nurture problem-solving skills, adaptability, and technological awareness from an early age. Beyond simply broadening students’ technological insights, the program also contributes to the enhancement of their competencies and preparedness in facing challenges of the digital era, ensuring that they can continue to grow as innovative learners and future innovators.